Perdidas de suelo por erosion en sistemas de produccion de cafe con cultivos intercalados - Quiroz M, T.=700 1 Hincapie G, E.
(En, Es)
ilus., 14 ref.
Keywords: ZEA MAYS; PHASEOLUS VULGARIS; MANIHOT ESCULENTA; DETERIORO DEL SUELO; ESCORRENTIA; CULTIVO INTERCALADO; LUCHA INTEGRADA; MALEZAS; COMPETICION VEGETAL; COLOMBIA; ARVENSES; CENICAFE